Analisis Pengaruh Komunikasi dan Pengawasan Kerja Terhadap Produktivitas Kerja Perangkat Kenagarian Batu Manjulur Kecamatan Kupitan Kabupaten Sijunjung - Erlina Indri Yeni; Liza Zulbahri (Journal on Education, 2023)
The purpose of this study was to analyze the influence of communication and work supervision on the work productivity of the employees of the Nagari Batu Manjulur Government, Kupitan District, Sijunjung Regency. The research method used is descriptive quantitative. the population totaled 62 employees, so that from this population there were a sample of 62 respondents, using probability sampling technique and sampling using saturated samples. Data collection methods used are observation, questionnaires and library research. data analysis technique used is multiple linear regression, t test, f test and the coefficient of determination. Based on multiple linear regression analysis, the variables of communication and work supervision partially and simultaneously on the work productivity of Nagari Batu Manjulur Government employees, Kupitan District, Sijunjung Regency, obtained Y = 1.874 + 0.884X1 + 0.446X2 + e the results of the t-test conducted found that the communication variable has a significant effect on the work productivity of Nagari Batu Manjulur Government employees, Kupitan District, Sijunjung Regency because the t test produces a tcount > ttable 11.766 > 1.671 and a significant 0.000< 0.05 the work supervision variable has a significant effect on the work productivity of Nagari Batu Manjulur Government employees, Kupitan District, Sijunjung Regency, because the t test produces a t count > t table, namely 8.131 > 1.671 and a significant 0.000 < 0.05 the f test results prove that communication and work supervision simultaneously have a significant effect on the work productivity of Nagari Batu Manjulur Government employees, Kupitan District, Sijunjung Regency, because the F test produces Fcount > Ftable, namely 509.931 > 3.153 and a significant level of 0.000 <0.05. while the results of the coefficient of determination were 94.4%.